Documenting occupant models for building performance simulation: a state-of-the-art. Issue 5 (3rd September 2022) - Vellei, Marika; Azar, Elie; Bandurski, Karol; Berger, Christiane; Carlucci, Salvatore; Dong, Bing; Favero, Matteo; Mahdavi, Ardeshir; Schweiker, Marcel
Abstract : The number of occupancy and occupant behaviour models developed for building performance simulation (BPS) has steadily increased for the past four decades. However, their use is still limited in practice. This is partly due to the difficulty in understanding their utility and to the challenges related to their implementation into BPS. Both problems can be attributed to the lack of a framework for their description and communication. In this paper, we fill this gap by introducing a framework to document occupant models, that represents the state-of-the-art of available information on the topic. The framework consists of four blocks (description, development, evaluation, and implementation) and can also be regarded as a guideline to help researchers communicate their models transparently. Based on a systematic review, we verify to which degree existing academic papers on occupant models meet the framework, thus providing a self-critical assessment of the state-of-the-art of occupant models' documentation.